2004
DOI: 10.1037/1053-0797.14.1.21
|View full text |Cite
|
Sign up to set email alerts
|

The Dream Will Tell: Militant Muslim Dreaming in the Context of Traditional and Contemporary Islamic Dream Theory and Practice.

Abstract: Al-Qaeda and Taliban leadership and membership appear to have been motivated, inspired, and guided by certain dreams. Their understanding of dreams seems to draw at least partly on traditional and contemporary Islamic dream theories. If this hypothesis is correct, then there is a need for the urgent study of Islamic Jihadist political/religious conversion and guidance dreams across the Middle East. The dream-as experienced, reported, and interpreted-is now a significant aspect of the global conflict between Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…Islam, for example, largely seems to have been left out of the study of religion and personality. When authors do consider psychology in the context of Islam, they almost always write from the perspective of either mental health (e.g., Ali, Liu, & Humedian, 2004;Ansari, 2002;Fayek, 2004;Sheridan & North, 2004) or the psychology of Islamic extremism (e.g., DeMause, 2002;Edgar, 2004;Gibbs, 2005), rather than focus on how ideas within an Islamic cultural context might affect normal personality development or behavior. Given the size of the world's Muslim population, this seems to be an area deserving more attention from personality researchers.…”
Section: Personality Psychology and Religionmentioning
confidence: 99%
“…Islam, for example, largely seems to have been left out of the study of religion and personality. When authors do consider psychology in the context of Islam, they almost always write from the perspective of either mental health (e.g., Ali, Liu, & Humedian, 2004;Ansari, 2002;Fayek, 2004;Sheridan & North, 2004) or the psychology of Islamic extremism (e.g., DeMause, 2002;Edgar, 2004;Gibbs, 2005), rather than focus on how ideas within an Islamic cultural context might affect normal personality development or behavior. Given the size of the world's Muslim population, this seems to be an area deserving more attention from personality researchers.…”
Section: Personality Psychology and Religionmentioning
confidence: 99%
“…56 Th is continues to be the case today among some sections of the Muslim community-Iain Edgar, for example, has discussed the signifi cance of dreams within militant Islamic groups such as the Taliban and Al-Qaeda. 57 Lest this relationship be understood as a purely Muslim phenomenon, though, it has also been observed in other parts of the world. In eighteenth-century Russia, dreams perceived to have political signifi cance were more likely to be accepted by sceptical elites than would otherwise have been the case, 58 and as late as the mid-nineteenth century American politicians gave credence to one of Abraham Lincoln's dreams, which they believed had foretold his death.…”
Section: Dreams and Authoritymentioning
confidence: 95%
“…At their core are often cadres of dedicated members focused on a charismatic leader. Iain Edgar has analyzed jihadist dreams, including those by Al-Qaeda and Taliban leaders, and found that dreams both motivate conversion to jihadism and are regarded as divinatory predictions and prescriptions of future events and actions, especially when the dreamers are divinely inspired charismatic leaders (Edgar 2004(Edgar , 2006(Edgar ,2007(Edgar , 2008. I have argued, in response to Peter van der Veer's view (2004) that charisma had ceased to be a useful concept in the modern world, that Against the skeptical view of charisma as irrelevant to postcolonial or globalization theory, one may argue that transnational communication has enhanced the status of religious charismatic figures and their organizational reach.…”
Section: See Contributions To the Social Analysis Forum The World Tradementioning
confidence: 98%
“…A salient further distinction characterizing Islamist rhetoric is between "millennial" discourses that invoke a Utopian kingdom on earth and a return to the pristine time ofthe Prophet, on the one hand, and on the other, "jihadist" discourses that promote martyrdom as the gateway to paradise, the kingdom of heaven (P. Werbner 2004). Jihadists often live in a world where dreams of paradise seem more real that the mundane reality around them (Edgar 2004). Further important ideological distinctions are between those aiming to install an Islamic state through the ballot box (as in the case of Jamaat-e-Islami in Pakistan); jihadists, who espouse the violent overthrow of Muslim and other regimes (as in the case of Hizb-ut-Tahrir or Al Muhajairun); neofundamentalists, who seek to "purify" and reform the person as a precondition to the ideal Islamic state, whether peacefully (as in the case of Tabligh-i-Islam) or violently (as in the case ofthe Taliban); and those who espouse martyrdom, the fight to the death against so-called infidels (as in the case of AlQaeda).…”
Section: See Contributions To the Social Analysis Forum The World Tradementioning
confidence: 99%